1977
DOI: 10.1161/01.res.41.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic properties of the diastolic left ventricle in the conscious dog.

Abstract: SUMMARY The mechanical properties of the normal left ventricular wall during diastole were studied in 15 chronically instrumented, conscious dogs. Left ventricular minor and major axis diameters and equatorial wall thickness were measured with implanted pulse-transit ultrasonic dimension transducers. Left ventricular and pleural pressures were measured with high fidelity micromanometers. Circumferential mural stress was calculated by using an ellipsoidal shell theory; circumferential strain was calculated by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0
2

Year Published

1980
1980
2002
2002

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(62 citation statements)
references
References 55 publications
1
59
0
2
Order By: Relevance
“…This difference between chamber and myocardial properties is important because chamber properties are dependent on the size and geometry of the left ventricle (not normalized data), but are directly related to clinical symptoms and diastolic compliance failure, whereas myocardial properties reflect mechanical and structural factors of the myocardium per se (normalized data for size and geometry) and are not necessarily related to clinical symptoms and diastolic compliance failure. A viscoelastic model for the determination of chamber and myocardial properties was used since it has been demonstrated that the diastolic stress-strain relationships are characterized more adequately by a viscoelastic than a simple elastic relationship with a monoexponential curve fit.4 12 Our data show only minor viscous effects for the whole ventricle when chamber properties are studied, but increased viscous effects in patients with aortic valve disease before surgery when myocardial properties are examined (table 3). Thus, overall viscous effects seem to be small, but myocardial viscous effects seem to be important in patients with myocardial hypertrophy.…”
Section: Discussionmentioning
confidence: 78%
“…This difference between chamber and myocardial properties is important because chamber properties are dependent on the size and geometry of the left ventricle (not normalized data), but are directly related to clinical symptoms and diastolic compliance failure, whereas myocardial properties reflect mechanical and structural factors of the myocardium per se (normalized data for size and geometry) and are not necessarily related to clinical symptoms and diastolic compliance failure. A viscoelastic model for the determination of chamber and myocardial properties was used since it has been demonstrated that the diastolic stress-strain relationships are characterized more adequately by a viscoelastic than a simple elastic relationship with a monoexponential curve fit.4 12 Our data show only minor viscous effects for the whole ventricle when chamber properties are studied, but increased viscous effects in patients with aortic valve disease before surgery when myocardial properties are examined (table 3). Thus, overall viscous effects seem to be small, but myocardial viscous effects seem to be important in patients with myocardial hypertrophy.…”
Section: Discussionmentioning
confidence: 78%
“…The accuracy of this technique was illustrated by the finding that subtracting pleural pressure from intracavitary left ventricular pressure virtually eliminated respiratory variation in the diastolic pressuredimension relationship. 10 Thus, using the pleural pressure on the surface of the heart as the external pressure, decreased transmural filling pressures of both ventricles were observed with PEEP in all animal preparations and in man. Therefore, the increased filling pressures reported previously must have been artifactual, possibly because of inaccurate pleural pressure measurements or the use of mean atrial pressure as the absolute index of ventricular filling.…”
Section: Discussionmentioning
confidence: 81%
“…Thus, the prolate spheroid model and the results of the group 1 experiments appear to be valid. The right ventricular o 0 PEEP septal-free wall diameter remained relatively constant o 10 PEEP as the airway pressure was increased. To more fully 20PEEP understand these observations, the experiment illus-3OPEEP trated in figure 8 was performed.…”
Section: Discussionmentioning
confidence: 92%
“…Co was measured during maximum vena caval occlusion. Emax and the static diastolic curve were generated by selecting data from 10 to 20 cycles during an approximately 20 sec vena caval occlusion (Rankin et al 1977;Sodums et al 1984). DP/ dE and da/de correspond to the instantaneous chamber and myocardial stiffness of the LV at a specific LVP and stress (Alyono et al 1984).…”
Section: Methodsmentioning
confidence: 99%